Relations between food intake, psychological distress, and gastrointestinal symptoms: A diary study. Issue 7 (August 2019) - Clevers, Egbert; Törnblom, Hans; Simrén, Magnus; Tack, Jan; Van Oudenhove, Lukas
Background: Gastrointestinal symptoms can be triggered by food intake and psychological distress, but individual-level research on food–symptom and stress–symptom associations is scarce. Objective: We aimed to identify associations between food intake, psychological distress and gastrointestinal symptoms, and their implications for personalised clinical management. Methods: Through the mobile phone application mySymptoms, 163 users kept, for a median of five weeks, a diary of food intake, psychological distress and gastrointestinal symptoms. We quantified associations between these on the individual level. The presence of individual-level associations was compared over latent classes of daily symptom patterns. Results: Various gastrointestinal symptoms had demonstrable food–symptom associations (heartburn: 73%, discomfort: 67%, diarrhoea: 57%, bloating: 53%, and gas: 48%). Food–symptom associations for pain in the abdomen (33%) were concentrated in the latent class of individuals with pain in the morning (68%), rather than those with pain in the evening and night (27% and 10%, respectively, p < 0.001). Stress–symptom relations were also found, although only 18% of individuals reported psychological distress. Conclusion: Personal food–symptom and stress–symptom relations can be detected, and may translate into specific daily symptom patterns. A next step will be to let personal food–symptom and stress–symptom relations serve as the basis for personalised clinical management.